ANALISIS KERUGIAN EKONOMIS DAN PEMETAAN SEBARAN SERANGAN RAYAP PADA BANGUNAN SMP NEGERI DI KOTA PEKANBARU - Meita Endasura; Yunus Afifuddin; Lutfhi Hakim (Program studi Kehutanan USU, 2015)
Termites are pests that can cause the damage to buildings and can make a big economic losses.The Junior High school building is one of the object that target by termites which haven’t been studied and investigated. This study intend to get the value of economic losses caused by termites attack toward the Junior High School buildings in Pekanbaru. The dis- tribution of termites mapped using Geographic Information System (GIS). The method used was direct observation, in- terviews using questionnaires and analyze the damage to buildings using a tally sheet. The result showed that 75% of The Junior High School building were attacked by the termites and 25% of The Junior High School building weren’t at- tacked by the termites.48% of the The Junior High School building have medium damage and 27 % have small dam- age.Termite species found are Cryptotermes cynocephalus Light for dry wood termites and Microtermes inspiratus Kemmer for subterranean termites Keywords: Termites, The Junior High School buildings, Economic losses, Geographic information system (GIS)